Global Transactions: Managing Risks in Global Sourcing - Wilding, Richard D.; Braithwaite, Alan (Cranfield University, 2006)
The policy of global sourcing is a strategic imperative for many businesses; it has raised the competitive ‘bar’ to the point where it has become a qualifier for survival rather than a competitive edge in its own right. There has been huge investment to secure low unit costs through the chain and drive volume and margin simultaneously. The low wage areas of Asia have attracted high labour content work from garments to computers to consumer products to engineer